Quantização de partículas com spin - Tilles, P. F. C [UNESP] (2007)
Aclassical relativistic particleis described by means of Dirac's formalism for constrained systems, where the constraints come from the reparametrization invariance required by an explicitly covariant theory. We introduce spin degrees of freedom via Grassman variables, which leads directly to the concept of supersymmetry in the theory. The equations of motion and quantization are considered both for the spin 0 and 1/2 free theories, and for the eletromagnetic interaction. The ﬁrst class constraints algebra is extended to describe spin N/2 particles, which include spin 1 representations. The quantum theory obtained is compared to the classical theory of ﬁelds